Engineering Schottky barrier in vertical graphene/InN heterostructure. (1st June 2022) - Liu, Yuhang; Li, Hong; Liu, Fengbin; Sun, Shuai; Zhou, Gang; Qing, Tao; Zhang, Shaohua; Lu, Jing
Abstract: In recent years, van der Waals stacked heterostructures (vdWHs) have gained much study interest for enhancing nanoelectronics' performance. We take the first-principles methods to study the interface contact characters of the graphene/InN vdWH under the interlayer coupling and electric field. The natural electronic characters of both the graphene and InN components keep intact at the equilibrium interlayer distance with an n -type Schottky contact. Impressively, it tunes to Ohmic contact when the interlayer distance increases to 4.73 Å or the applying negative electric field increases to −0.42 V/Å, while it converts to p -type Schottky contact under a positive electric field greater than 0.2 V/Å. These findings are of great significance for the application of graphene/InN vdWH in high-performance nanoelectronics. Graphical abstract: Image 1 Highlights: Contact properties of graphene/InN vdW heterostructures are studied within DFT simulation. Narrow n-type Schottky barrier is obtained at equilibrium state. Ohmic contact can be acquired through changing the interlayer coupling or applying an external electric field. The graphene/InN vdW heterostructure is a promising candidate for the nanoelectronics.